The effect of Phase 1 periodontal treatment on the salivary RANKL/OPG ratio in severe chronic periodontitis - Ansari Moghadam S; Sarani S; Alijani E; Ansari Moghadam A (Dove Medical Press, 2019)
Somaye Ansari Moghadam,1 Somaye Sarani,2 Ebrahim Alijani,3 Alireza Ansari Moghadam41Department of Periodontology, Oral and Dental Disease Research Center, Zahedan University of Medical Sciences, Zahedan, Iran; 2Oral and Dental Disease Research Center, Zahedan University of Medical Sciences, Zahedan, Iran; 3Department of Clinical Immunology Research Center, Zahedan University of Medical Sciences, Zahedan, Iran; 4Department of Health Promotion Research Center, Zahedan University of Medical Sciences, Zahedan, IranBackground: RANKL and OPG play an important role in bone resorption. The RANKL/OPG ratio increases in periodontal disease. The present study was conducted to evaluate the effect of Phase 1 periodontal treatment on the salivary RANKL/OPG ratio in patients with severe chronic periodontitis.Materials and methods: Saliva samples were collected from 13 patients with severe chronic periodontitis and 14 healthy controls at baseline and then four weeks after the treatment using unstimulated spitting. The salivary levels of RANKL, OPG and RANKL/OPG ratio were investigated using the ELISA method.Results: The findings of this study showed that the mean RANKL/OPG ratio was significantly higher in the patients with periodontal disease than in the healthy controls (P=0.001). Also, the RANKL/OPG ratio was significantly higher in the patients with a higher mean CAL (P=0/004). The comparison of the salivary RANKL/OPG ratio in patients with periodontal disease before and four weeks after the treatment showed a significant reduction in this value four weeks after the periodontal treatment (P=0/001).Conclusion: The results of this study showed a direct relationship between the RANKL/OPG ratio and the severity of periodontal disease. Phase 1 of periodontal treatment was found to be effective in reducing the RANKL/OPG ratio. In other words, the RANKL/OPG ratio can be a good predictor of treatment success. Further long-term studies with larger sample sizes are required for confirming these results.Keywords: chronic periodontitis, salivary levels, ratio, RANKL, OPG